On the frequency spectrum of the normal waves in a prestressed compressible layer interacting with the layer of an ideal fluid - Bahno, O.M. (Reports of the National Academy of Sciences of Ukraine, 2015)
Basing on the three-dimensional linearized equations of the elasticity theory of finite deformations for a solid and the three-dimensional linearized Euler equations for an ideal compressible fluid, the dispersion curves of normal waves in hydroelastic system in a wide range of frequencies are constructed. The effects of initial stresses in a predeformed compressible elastic layer and of the fluid layer thickness on the phase velocities of modes in a hydroelastic waveguide for both thin and thick elastic layers are analyzed.